2002
DOI: 10.1002/j.1551-8833.2002.tb09562.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring oxidant species in ELECTROLYZED salt brine solutions

Abstract: The electrolysis of salt brine solutions by onsite generators produces chlorine (free available chlorine [FAC = Cl2, HOCl, and OCl–]) at concentrations ranging from 200 to 1,000 mg/L. There is some speculation that the electrolysis of salt brine also produces chlorine dioxide (ClO2) and ozone (O3). The analytical methods frequently cited for measuring ClO2 and O3 in anolyte liquors following salt brine electrolysis are the DPD and indigotrisulfonate methods. These analytical procedures are routinely used to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The formation of chlorine dioxide from chloride (Cl − ) and chlorite (ClO 2 − ) containing aqueous solution by electrochemical mechanism can be considered to occur according to the following equations [24,[33][34][35][36]:…”
Section: General Electrochemical Reactions In Clo 2 Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of chlorine dioxide from chloride (Cl − ) and chlorite (ClO 2 − ) containing aqueous solution by electrochemical mechanism can be considered to occur according to the following equations [24,[33][34][35][36]:…”
Section: General Electrochemical Reactions In Clo 2 Formationmentioning
confidence: 99%
“…The main difficulty concerning with these studies is that all of them are as patents, and explicit details on cell design, experimental parameters and conditions, etc., are not accessible. Some of the available literature from publications by Gordon and his co-workers [32][33][34][35][36] and Bergmann group [24,[37][38][39] are mainly related to analyzing chlorine chemistry and problems of by-product analysis for chlorination, or in liquors of chlorine disinfectants produced electrochemically.…”
Section: Introductionmentioning
confidence: 99%
“…The system is currently operating widely for chlorine boosting stations in a multi-regional water supply, small community water treatment systems and distribution reservoirs in Korea. However, the mixed oxidants generation system has not been evaluated on the concentration and species of each oxidant in the mixed oxidants due to the lack of effective analytical methods [5]. Thus, there are still conflicts on the efficiency of mixed oxidants as disinfectant.…”
Section: Introductionmentioning
confidence: 99%
“…Based from previously done studies [4,[10][11][12][13], it was reported that "mixed oxidants" were more effective than chlorine in inactivating microorganisms, removing biofilm, and reducing DBP formation and chlorinous odor. Still, the exact composition and concentration of the produced oxidants in the "mixed oxidants" remain unclear [6,14]. Moreover, in most previous studies [10][11][12], commercial sodium hypochlorite solution was used as chlorine disinfectant instead of chlorine gas.…”
Section: Introductionmentioning
confidence: 99%